Subtle changes in perivascular endometrial mesenchymal stem cells after local endometrial injury in recurrent implantation failure - Yiping Fan; Ryan Wai Kheong Lee; Xiang Wen Ng; Caroline E. Gargett; Jerry Kok Yen Chan (Scientific Reports, 2023)
Abstract Improvements in reproductive techniques have resulted in the live birth rates from IVF procedures increasing from 5% to approximately 30% in recent decades but has plateaued since. Emerging preclinical and clinical data implicates endometrial receptivity deficiencies in patients with recurrent implantation failure (RIF) as the predominant factor hindering successful implantation. Mechanisms on how local endometrial injury (LEI) improves implantation rates in patients with RIF are currently unknown. We hypothesized that LEI may influence perivascular endometrial mesenchymal stem/progenitor cells (eMSCs) which are thought to regenerate the stromal vascular component of the functional layer every month. Here, we assessed the effect of LEI on the proportion and function of eMSCs present in consecutive LEI biopsies. Consecutive paired mid-luteal phase endometrial biopsies obtained from patients with RIF were digested to single cells and the proportion of SUSD2-expressing cells determined. Growth kinetics and decidualization were compared between the consecutive LEI samples. A mid-luteal LEI altered the decidualization capacity of SUSD2+ eMSCs in women with RIF, but not their proportion or clonogenicity. With the potential of LEI to improve IVF outcomes in women with RIF, additional investigations are needed to understand the impact of the altered decidualization response in eMSCs.